Education as a key in career building - Hitka, Miloš; Štarchoň, Peter; Lorincová, Silvia; Caha, Zdeněk (Journal of Business Economics and Management, 2021)
Human resources in companies are gaining increasingly more strategic meaning by its ability to influence reaching company goals. The task of a manager is to understand the fact that every employee is different, has different needs, goals, and ambitions, is motivated by something else in every stage of career ladder. The aim of the paper is to define the influence of education in building the employee’s career. The presumption if the level of education has influence on the career motivation factors is verified on the sample of 3,720 respondents. The results of the research have confirmed that the employee’s career is influenced by the level of education significantly. Motivation factors education and personal growth, applying own skills, self-fulfillment, and autonomous decision-making are perceived differently in terms of importance and gender. Therefore, it is recommended the company managers to include into leading of employee’s career also the level of education in the context of gender that influences employee’s needs and interests.